PERAN PENERIMAAN SOSIAL TERHADAP PSIKOPATOLOGI PERKEMBANGAN SINDROM TOURETTE PADA PEREMPUAN - Ellen Prima (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2015)
Abstract: One type of developmental psychopathology that often occurs in childhood is Tourette's syndrome which begins with mild symptoms such as mild tic movements of the face, head or hands. Tic will often arise when children feel pressured (stressed) and their emotional become unstability. It increases along with the age, it deals with the development of body parts such as legs and other body parts. Tourette's syndrome can happen to everyone of all ethnic groups. Tourette's syndrome is due to genetic and environmental influences, infections (damage) in the brain, the effects of neuroimmunological, disruption experienced in the prenatal and birth time, psychosocial stress, and the influence of androgens. Therefore, social (environment) acceptance helps a person to adapt well and be able to use its full potential, especially for people suffering from disorders one of which is of Tourette's syndrome. Family support is very important that the person feel confident and be positive when he/she is outside. Kata Kunci: Psikopatologi Perkembangan, Penerimaan Sosial, Sindrom Tourette